2022
DOI: 10.1371/journal.pcbi.1010125
|View full text |Cite
|
Sign up to set email alerts
|

Superinfection exclusion: A viral strategy with short-term benefits and long-term drawbacks

Abstract: Viral superinfection occurs when multiple viral particles subsequently infect the same host. In nature, several viral species are found to have evolved diverse mechanisms to prevent superinfection (superinfection exclusion) but how this strategic choice impacts the fate of mutations in the viral population remains unclear. Using stochastic simulations, we find that genetic drift is suppressed when superinfection occurs, thus facilitating the fixation of beneficial mutations and the removal of deleterious ones.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 68 publications
(99 reference statements)
1
16
1
Order By: Relevance
“…Namely, it allows the semi-infectious progeny virions which make up the majority of the viral population (10) to complement each other. Coinfection allows these otherwise "non-infectious" virus particles to contribute to productive infections (44,45).Stochastic simulations in bacteriophage have demonstrated that viral populations that are incapable of initiating SIE are more able to fix beneficial mutations (46). Therefore, unrestricted coinfection between the progeny of a virus could help to maintain viral population fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, it allows the semi-infectious progeny virions which make up the majority of the viral population (10) to complement each other. Coinfection allows these otherwise "non-infectious" virus particles to contribute to productive infections (44,45).Stochastic simulations in bacteriophage have demonstrated that viral populations that are incapable of initiating SIE are more able to fix beneficial mutations (46). Therefore, unrestricted coinfection between the progeny of a virus could help to maintain viral population fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Waning immunity has been included previously in a range of epidemiological models (62,63), and is a target for future addition to the modelling framework presented here, along with consideration of heterogeneity in immunity between previously infected hosts. Additionally, similar investigations to those conducted here could be undertaken for scenarios in which multiple viruses are co-circulating (potentially allowing for superinfection (64)). This could include analyses of epidemiological dynamics beyond the early phase of the outbreak of the novel variant, after it has invaded the host population.…”
Section: Discussionmentioning
confidence: 96%
“…For IAV, genome complementation within an infected lesion would mean that the semi-infectious progeny virions that make up around 90% the viral population could contribute to productive infection [ 44 46 ]. In a similar way, stochastic simulations of the effects of SIE in bacteriophage have demonstrated that viral populations that are incapable of initiating SIE would be less able to fix beneficial mutations [ 47 ]. We suggest that for IAV coinfection between the progeny of a virus could help to maintain viral population fitness.…”
Section: Discussionmentioning
confidence: 99%